Strategi Pemasaran di YouTube Melalui Subscriber & Komentar dan Perspektif Persuader Terhadap Keputusan Pembelian - Ana Ramadhayanti (Departemen Manajemen, Universitas Syiah Kuala, 2019)
Today's marketing is highly sought after by products that are marketed through social media or through print media. One of the social media that is not less attractive to many people is YouTube. Through YouTube media consumers are interested in the products offered. The marketing strategy through YouTube attracts consumers because most people tend to spend more time accessing YouTube. This research uses quantitative methods by collecting data through distributing questionnaires to consumers who shop through YouTube. After conducting the research, the results of the study showed that there was a significant and positive influence between the Marketing Strategy variables on the Purchase Decision, while the Persuader Perspective variable also significantly and positively affected the Purchasing Decision. After that, together between the Marketing Strategy variables and Persuader's Perspective also influence the Purchasing Decision.Keywords Subscriber, YouTube, Marketing Strategy.